(+)-Dehydrovomifoliol Alleviates Oleic Acid-Induced Lipid Accumulation in HepG2 Cells via the PPARα–FGF21 Pathway - Xi, Yiyuan; Zheng, Jujia; Xie, Wei; Xu, Xiangwei; Cho, Namki; Zhou, Xudong; Yu, Xiaomin (Frontiers in Pharmacology, 2021)
An overload of hepatic fatty acids, such as oleic acid (OA), is a key trigger of non-alcoholic fatty liver disease (NAFLD). Here, we investigated whether Artemisia frigida, a valuable traditional medicine used to treat various diseases, could mitigate OA-induced lipid accumulation in HepG2 cells. Then, to identify the active substances in A. frigida, a phytochemistry investigation was conducted using a bioassay-guided isolation method. Consequently, one terpene (1) and one flavone (2) were identified. Compound 1 ((+)-dehydrovomifoliol) exhibited potent effects against lipid accumulation in OA-induced HepG2 cells, without causing cyto-toxicity. Notably, treatment with (+)-dehydrovomifoliol decreased the expression levels of three genes related to lipogenesis (SREBP1, ACC, and FASN) and increased those of three genes related to fatty acid oxidation (PPARα, ACOX1, and FGF21). In addition, similar results were observed for SREBP1, PPARα, and FGF21 protein levels. The effects of (+)-dehydrovomifoliol were partially reversed by treatment with the PPARα antagonist GW6471, indicating the important role of the PPARα–FGF21 axis in the effects of (+)-dehydrovomifoliol. Based on its effects on hepatic lipogenesis and fatty acid oxidation signaling via the PPARα–FGF21 axis, (+)-dehydrovomifoliol isolated from A. frigida could be a useful early lead compound for developing new drugs for NAFLD prevention.